Perencanaan Tenaga Kerja dan Kompensasi Stratejik Yang Meningkatkan Kepuasan Kerja Karyawan: Studi Pustaka Media Mainstream - Putri Martiza, Shanata; Asyifa, Zahra (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to examine the role of workforce planning and strategic compensation in enhancing employee job satisfaction based on a literature review of mainstream media sources. Current labor issues reported in national media highlight increasing job dissatisfaction, high turnover rates, workload imbalance, and demands for fairer compensation, emphasizing the urgency of integrating workforce planning and compensation strategies in modern organizational management. This research applies a qualitative approach through document analysis by collecting data from mainstream media publications and relevant academic sources that reported employment-related topics between 2020 and 2025. The findings reveal that well-structured workforce planning contributes to more effective task distribution and a greater sense of job security, while strategic compensation, both financial and non-financial, significantly increases motivation and employee recognition. In conclusion, the synergy between workforce planning and strategic compensation becomes a determinant factor in achieving sustainable job satisfaction, enabling organizations to create a productive, healthy, and competitive working environment.